Environmental impact assessment in livestock and poultry: public participation - Kozmuliak, Kateryna (My University, 2018)
The article is devoted to the analysis of the state of the legal regulation of the environmental impact assessment, which is carried out for livestock and poultry complexes. The work analyzes the requirements of the EU and Ukraine acts on the list of objects to be covered by the EIA procedure. Attention is paid to the issues of public participation in the discussion of planned activities. The requirements for the organization of public hearings have been analyzed in detail, a number of shortcomings have been identified that do not contribute to the effectiveness of the procedure and equality of the participants in such discussions. An attempt is made to formulate possible ways to eliminate the identified shortcomings. The author also analyzed the place and possibilities of mediation of conflicts that arise when discussing projects for the placement of livestock and poultry complexes. It is concluded that mediation can be one of the effective ways of making a coherent decision and resolving disputes in the EIA process.
Keywords: legal regulation of livestock; legal regulation of poultry breeding; environmental impact assessment; public participation; mediation; environmental protection; Ukraine